Exploring the Occurrence Characteristics of Microplastics in Typical Maize Farmland Soils With Long-Term Plastic Film Mulching in Northern China - Zhang, Jiajia; Zou, Guoyuan; Wang, Xuexia; Ding, Wencheng; Xu, Li; Liu, Baoyin; Mu, Yunsen; Zhu, Xuran; Song, Lianjie; Chen, Yanhua (Frontiers in Marine Science, 2021)
Microplastics pollution has been threatening the global environmental security, in which agricultural activities are considered as a main source of microplastics occurrence in soils. However, little is known about the occurrence characteristics of microplastics in agricultural soils with long-term plastic film mulching. Therefore, the abundance, distribution, and composition of microplastics were investigated by analyzing 225 soil samples collected from typical maize (Zea mays L.) planting zones with and without long-term (>20 years) plastic film mulching in northern China. Microplastics abundance in mulched soils (754 ± 477 items kg–1) was significantly higher than that in non-mulched soils (376 ± 149 items kg–1), which indicated that plastic film mulching contributed half of microplastics in soils. Moreover, microplastics abundance was significantly positively related to the length of time with film mulching applied. The percentage of microplastics <0.5 mm in mulched soils (50.9%) was significantly lower than that in non-mulched soils (62.2%). Microplastics abundance and size in mulched and non-mulched soils decreased with increased soil depth. Most microplastics were fragments of polypropylene, films of polyethylene, and fibers of polyester. The proportion of films in mulched soils was significantly higher than in non-mulched soils, whereas that of fibers was significantly higher in non-mulched soils. This study confirmed that long-term plastic film mulching increases microplastics pollution in agricultural soils, warranting further evaluation of the associated ecological risks of microplastics in soil ecosystems.